The Critical Issues of Knowledge Management and Sharing across Service Agencies - James, Natalie (European Journal of Information and Knowledge Management, 2022)
Purpose: Government agencies are mainly known as knowledge-intensive organizations. In order to exploit effective knowledge sharing, they have to develop practical knowledge sharing implementation approaches. Nevertheless, strong demand and expectation from citizens for efficient service delivery, coupled with global challenges in the knowledge-based economy have fuelled the need for government agencies to consider the effective implementation of knowledge sharing as a strategy to improve service delivery. Effective knowledge-sharing initiatives have the potential to benefit government agencies in view of their role. This paper aims to identify the core issues in knowledge-sharing initiatives that government agencies face in delivering effective policies, particularly in their role and influence in the construction industry. Results: Based on a critical review of literature on knowledge sharing in government agencies, dysfunctional bureaucracies, training, utilization of information technology, and adaptation to culture were identified as key issues. Unique contribution to theory, practice and policy: It is recommended that a balanced approach and support to these issues and challenges in implementing knowledge sharing initiatives are duly considered together with attention given to effective leadership, strategic alignments, capability, and capacity building among teams.